Pyrrolidine-containing peptides, JBIR-126, -148, and -149, from Streptomyces sp. NBRC 111228. Issue 39 (23rd September 2015) - Izumikawa, Miho; Kawahara, Teppei; Kagaya, Noritaka; Yamamura, Hideki; Hayakawa, Masayuki; Takagi, Motoki; Yoshida, Masahito; Doi, Takayuki; Shin-ya, Kazuo
Graphical abstract: Abstract: New pyrrolidine containing peptides JBIR-126 (1 ), JBIR-148 (2 ), and JBIR-149 (3 ) were isolated from a culture of Streptomyces sp. NBRC 111228 obtained from soil collected in the Okinawa Prefecture, Japan. The planar structures of 1, 2, and 3 were established based on 1D and 2D NMR, ESI-TOF-MS, IR, and UV spectra. The absolute configurations of amino acid residues were determined by Marfey's method. Compounds 1, 2, and 3 are structurally related to JBIR-34 and -35, in which an alanine residue is replaced by a unique pyrrolidine moiety.